2006
DOI: 10.1143/jjap.45.l1320
|View full text |Cite
|
Sign up to set email alerts
|

Growth of SiOx Nanofibers Using FeSi Substrates with Ga Droplets

Abstract: The growth of SiOx nanofibers on FeSi substrates with Ga droplets was examined. It is found that well-aligned, highly oriented nanofibers were grown in an orderly fashion with a high density from the substrates. Though the length of the nanofibers depends on the growth time and the growth temperature, their diameters were about 20 nm throughout the nanofibers grown under the examined growth conditions. The nanofibers are amorphous SiOx, and eliminate the broad photoluminescence around 460 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…As shown in Figure 1(d), it is observed that the highly oriented, well-aligned nanofibers grew in an orderly fashion with a high density on the substrates. It has also been observed that the nanofiber is thin with about a 20 nm uniform diameter, and the nanofiber is amorphous [12]. From the experimental results mentioned above, the nanofibers are found to be amorphous SiO x nanofibers.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…As shown in Figure 1(d), it is observed that the highly oriented, well-aligned nanofibers grew in an orderly fashion with a high density on the substrates. It has also been observed that the nanofiber is thin with about a 20 nm uniform diameter, and the nanofiber is amorphous [12]. From the experimental results mentioned above, the nanofibers are found to be amorphous SiO x nanofibers.…”
Section: Resultsmentioning
confidence: 87%
“…Even though Mg 2 Si and MgO are randomly distributed, the bundle structure maintains as the SiO x nanofiber bundle [15,12]. As shown in Figure 1(d), it is observed that the highly oriented, well-aligned nanofibers grew in an orderly fashion with a high density on the substrates.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 5(c) shows a cross-sectional SEM image of the SiO x nanofibers grown on an FeSi substrate with a Ga droplet at 900 ○ C for 114 h. It is observed that the highly-oriented and well-aligned SiO x nanofibers with the diameter of about 20 nm are grown in an orderly fashion with a high density on the substrates. 16 Figures 5(d) and 5(e) show SEM images of the Mg 2 Si/MgO composite nanowire bundles synthesized using SiO x nanofiber bundles as the starting materials at 450 ○ C and 630 ○ C, respectively. The nanowires synthesized at 450 ○ C completely maintain the morphology of the SiO x nanofibers, as shown in Fig.…”
Section: Syntheses Of Nanostructure Bundlesmentioning
confidence: 99%
“…They were thermally treated at 600 ○ C for 4 h. 15 Mg 2 Si/MgO nanowire bundles were synthesized by the heat treatment of SiO x nanofiber bundles in a Mg vapor. The amorphous SiO x nanofibers with diameters of 20 nm were grown by heat treatment of the FeSi substrates with Ga droplets at 900 for 114 h. 16 Mg balls (1.0 mm, 99%) and SiO x nanofiber bundles with the atomic ratio of Mg:SiO x ¼ 320:1 were placed in a loosely sealed glass container, which was loaded into a vacuum chamber. The heat treatment was performed at the temperature of 450 ○ C and 630 ○ C for 6 h with the vacuum pressure of 10 À6 Torr.…”
mentioning
confidence: 99%